The System for Monitoring of the Fast Vertical Oscillations of VEPP-3 SR Beam - Fedotov, M.G. (Physics procedia, 2016)
Due to the presence of a ripple on the output of various power sources, and mechanical vibrations the VEPP-3 wiggler beam is subject to certain perturbations (oscillations). Such disturbances can distort the results of precise experiments. At the same time the existing stabilization system of the synchrotron radiation (SR) beam works with a large averaging times and almost not sensitive to these disturbances. The differential high-speed detector based on pin-photodiodes and electronic processing circuits (that provide filtering and correlated double sampling of the signals) was developed for observation of the SR beam vertical oscillations. Detector is supplemented by electromechanical system for automatically adjustment of the sensor in beam center and allows to record slow displacement with a resolution of up to 0.2 microns. It is expected that in the future this system can be connected to fast correctors of VEPP-3 storage ring for feedback suppression of the beam oscillations.